Instagram as a tool of `social navigation`: women`s soccer in the Islamic Republic of Iran - between censorship and (r)evolution - Azad, C. (Soccer & Society, 2024)
From the beginning of the COVID-19 pandemic, Instagram has proven to be a very relevant source of information about Iranian women`s soccer. The growing popularity of female professional football players, particularly members of the national team, tends to make their discourse particularly audible, reaching thousands of people on issues that concern discrimination against the Iranian female population in general as well as inequalities of treatment between men and women. By investing a male-dominated domain such as football and by imposing their voice, presence and visibility on the digital space, female football players tend to challenge the authority of the Iranian State in a spontaneous, sustained, original and unorganized way. The main obstacle to the development of the discipline is defined, following the testimonies described in this article, as the lack of media visibility of women`s soccer in the traditional media. This is not unique to Iran, as I explain, but linked to a political strategy to regulate the visibility of women, especially the female body, in the public space. I chose to use the theoretical tool of social navigation to provide an understanding of the discourses and actions of resistance implemented by various female players, especially on Instagram. All of these social agents operate in a non-democratic socio-political environment and acting under particular circumstances.